Environmental risk perceptions of residential and commercial neighborhoods of petrol stations in Maiduguri Metropolis, Nigeria - Mshelia, A. M.; Salihu, A. C.; Ubachukwu, N. N.; Dibal, I. J. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Environment for decades has been subjected to varied degree of degradations majorly by anthropogenic activities at the detriment of its full potentials. In light of this, the paper evaluates environmental risk perceptions of residential and commercial outfits in the neighborhoods of petrol stations in Maiduguri metropolis. Data were collected quantitatively and qualitatively with the aid of questionnaires, interview schedules and literatures. Seventy (70) residential houses and 28 commercial shops within 100m radius proximity to 14 petrol stations were targeted at random; given 5 houses and 2 shops around each sampled station picked along 7 routes. From each sample, 1 respondent was picked purposively and issued questionnaire or administered interview. The results as revealed, 73.5% respondents complained of persistent inhalation of fuel-polluted air at their location due to their close proximities to the facilities. Whilst 67.5% claimed they do not derive benefits directly from the neighbourhood facilities. However, 81.9% respondents were compelled to live with the risk and hazard challenges perceived to be associated with the neighbourhood facilities, since they lack effective voice that could help to make a change. Given this, location and activities of petrol stations within human settlements are playing significant role in adding pollutants into the environment. Consequently, it seems obvious that in most of urban Nigeria, location of many obnoxious facilities like petrol stations have compromised stipulated guidelines; thereby heightening challenges confronting the weak. As such their presences are evidently chaotic and this is likely to continue without regards to basic environmental best practices.